2006
DOI: 10.1128/jvi.80.3.1181-1190.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell Growth on Hepatitis C Virus (HCV) Replication and a Mechanism of Cell Confluence-Based Inhibition of HCV RNA and Protein Expression

Abstract: An intimate relationship between hepatitis C virus (HCV) replication and the physiological state of the host liver cells has been reported. In particular, a highly reproducible and reversible inhibitory effect of high cell density on HCV replication was observed: high levels of HCV RNA and protein can be detected in actively growing cells but decline sharply when the replicon cells reach confluence. Arrested cell growth of confluent cells has been proposed to be responsible for the inhibitory effect. Indeed, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 33 publications
(55 reference statements)
2
54
0
Order By: Relevance
“…It has been reported that the growth state of the host cell can have detectable effects on the replication rate of HCV replicons (14,23,27). Because we wanted to ensure that our HCV IFN-␣ inhibition experiments were performed under conditions that limited any nonspecific effects IFN-␣ might have on the host cell, we initially monitored the effect that increasing IFN-␣ doses (i.e., 100, 250, 500, and 1,000 U/ml) had on Huh7 clone B cell viability and growth ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the growth state of the host cell can have detectable effects on the replication rate of HCV replicons (14,23,27). Because we wanted to ensure that our HCV IFN-␣ inhibition experiments were performed under conditions that limited any nonspecific effects IFN-␣ might have on the host cell, we initially monitored the effect that increasing IFN-␣ doses (i.e., 100, 250, 500, and 1,000 U/ml) had on Huh7 clone B cell viability and growth ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the impact of HCV replicon expression on the status of reprogrammingand hepatic progenitor cell-related proteins using GS5 and FCA4 cell lines (7,14,37). The GS5 cells are derived from the Huh7.5 hepatoma cell line that permits efficient replication of HCV.…”
Section: Resultsmentioning
confidence: 99%
“…The cells harbor a geneticin (G418)-selectable subgenomic HCV-1b replicon that encodes nonstructural proteins NS3 through NS5B and a functionally active NS5A-green fluorescent protein (GFP) chimera (34,37). The intensity of the GFP in GS5 cells indicates the replication efficiency of the replicon RNA (37). The cells were cultured in the absence of G418, followed by treatment with IFN-␣ and cyclosporine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, higher expression levels of these genes may facilitate the growth of Huh7.5.1-8 cells. Because HCV replication is known to vary between stages of cell growth (42)(43)(44), further investigations of the 6 genes identified in the present study are required to determine their roles in the HCV life cycle, including RNA replication.…”
Section: Discussionmentioning
confidence: 99%